Health seeking behavior among tuberculosis clients in a province of Thailand: A hospital-based study - Maneekul, Supreeya; Punpanich, Rattana; Siviroj, Penprapa (Health Science, Science and Technology Reviews, 2015)
The aim of the study was to examine the patterns of health seeking among 60 tuberculosis clients. The demographic data, health seeking behavior, and delays on presentation were collected. Three symptoms of cough, weight loss, and exhaustion were commonly encountered of 85.0, 78.3, and 66.6% respectively. The average client delay-to-health service was 11.3 weeks, and the majority of 85% waited at least 4-week postponement. Considerable delay exists between symptom onset and treatment initiating among the clients might be poor awareness and concern.